2010
DOI: 10.1021/ja103253d
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Steric Control of Regioselectivities in Rh(I)-Catalyzed (5 + 2) Cycloadditions: Experiment and Theory

Abstract: The first studies on the regioselectivity of Rh(I)-catalyzed (5 + 2) cycloadditions between vinylcyclopropanes (VCPs) and alkynes have been conducted experimentally and analyzed using density functional theory (DFT). The previously unexplored regiochemical consequences for this catalytic, intermolecular cycloaddition were determined by studying the reactions of several substituted VCPs with a range of unsymmetrical alkynes. Experimental trends were identified, and a predictive model was established. VCPs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 56 publications
0
75
0
2
Order By: Relevance
“…Adding to the patterns accessible by this logic was the fact that the chemistry is also extendable to the situation where the Diels-Alder diene contains a methyl substituent group at a terminal carbon 30 (Table 2). Once again, the levels of face selectivity in the cycloadditions were excellent, giving rise to the major adducts shown.…”
Section: Resultsmentioning
confidence: 99%
“…Adding to the patterns accessible by this logic was the fact that the chemistry is also extendable to the situation where the Diels-Alder diene contains a methyl substituent group at a terminal carbon 30 (Table 2). Once again, the levels of face selectivity in the cycloadditions were excellent, giving rise to the major adducts shown.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group [5] and that of others [20,21] have found that the regioselectivity for the cleavage of CÀC s bonds in cyclopropanes depends on the stereochemistry of the cyclopropane ring, the electronic properties of the substituents, and the nature of the metal catalysts. Our research group [5] and that of others [20,21] have found that the regioselectivity for the cleavage of CÀC s bonds in cyclopropanes depends on the stereochemistry of the cyclopropane ring, the electronic properties of the substituents, and the nature of the metal catalysts.…”
mentioning
confidence: 86%
“…A large array of different ACPs were transformed into the corresponding cis-fused bicyclohexenones with high yields and stereoselectivities by application of the optimized catalyst system consisting of [Rh(PPh 3 ) 3 Cl] and silver trifluoroacetate. All three tested catalyst systems-[{Rh(CO) 2 Cl} 2 ]/PPh 3 , [Rh(CO)(PPh 3 ) 2 Cl], and [Rh(PPh 3 ) 3 Cl]-displayed good to excellent activity and furnished the cis-fused bicyclohexenones in high stereoselectivity (cis/trans !…”
Section: Angewandte Highlightsmentioning
confidence: 99%
“…[1] Beside unsaturated substrates also strained carbocycles like cyclopropanes and cyclobutanes and their derivatives were identified to be suitable participants in these formal "higher-order" cycloaddition reactions. [3] In a recent publication Baik and Evans et al followed a somewhat different approach. The linkage of the single reaction participants in a chemo-, regio-, and stereoselective manner continues to display a significant challenge for preparative chemists since it provides the possibility to construct unusual structures difficult to assemble stepwise.…”
mentioning
confidence: 99%